Carbonation Induced Corrosion of R.C Structures-A Review - Chandra Harshitha, Bhaskar Sangoju, Vaishali G.Ghorpade, H. Sudarsana Rao (International Journal of Advanced Science and Technology, 2020)
Corrosion of rebar is one of the most critical problems that affect the long term durability of the reinforced concrete (RC) structures. Carbonation induced corrosion is one of the major types of corrosion that affects the service life of a structure, which in turn affect the sustainability of materials. Due to global warming, the CO2 concentration is increasing in the atmosphere that accelerate the carbonation process in the structures. Hence, it is important to study about the carbonation induced corrosion and understand it thoroughly for long term durability of structure. In the present study, different existing models such as Hakkinens, Kokubu and Nagataki, Umoto, Parrot, CEB, fib, Ekolu are reviewed for estimating the carbonation depth. The applicability, limitations of the models are studied in detail. The estimated carbonation depths are compared with the measured carbonation depths taken from the collected core samples and the relative errors are measured. Among the selected models Ekolu model is considered as reliable model based on the relative error, R2 value, data required, ease of collection of data,etc.